2015
DOI: 10.1080/19942060.2015.1071525
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of an offset jet with different velocity and offset ratios

Abstract: The present study examines the configuration of an offset jet issuing into either a quiescent medium or a moving stream (co-flowing). The mean velocity and turbulence characteristics of the turbulent offset jet have been investigated using a particle image velocimetry technique at three velocity ratios and for two offset ratios. A numerical simulation of a threedimensional offset jet has also been carried out by comparing the corresponding results with previous experimental data and our measurements. The numer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Miozzi et al [16] experimentally studied the effect of lateral wall placing at different distances from the jet outlet. Assoudi et al [17] investigated the mean velocity and turbulence characteristics of the turbulent offset jet using a particle image velocimetry technique at three velocity ratios and for two offset ratios. Also, Assoudi et al [18] experimentally and numerically investigated the flow field of variable density turbulent offset jet.…”
Section: Figure 1 Schematic Design Of Offset Jet Flowmentioning
confidence: 99%
“…Miozzi et al [16] experimentally studied the effect of lateral wall placing at different distances from the jet outlet. Assoudi et al [17] investigated the mean velocity and turbulence characteristics of the turbulent offset jet using a particle image velocimetry technique at three velocity ratios and for two offset ratios. Also, Assoudi et al [18] experimentally and numerically investigated the flow field of variable density turbulent offset jet.…”
Section: Figure 1 Schematic Design Of Offset Jet Flowmentioning
confidence: 99%
“…Regarding the inlet pressure influence on the characteristics of the parallel jet, Fujisawa [ 20 ] studied the interaction of two parallel plane jets under two different inlet velocities, and found that the interaction of the two parallel jets weakened with the decrease in the jet velocity ratio; Khazaei [ 21 ] found that the influence of the pressure of the dual parallel jet on the extraction effect is the most significant among many factors; Tian [ 22 ] studied the influence of pressure and nozzle target distance on jet impact pressure, and the results showed that both of them can effectively improve jet efficiency; Assoudi [ 23 ] found that the velocity ratio has a significant influence on the mean velocity and turbulence characteristics of the turbulent offset jet; Krishna Chandran [ 24 ] simulated the non-isothermal jet mixing phenomena and obtained result that suggested that the jets with a unity velocity ratio showed maximum temperature fluctuations; Wang [ 25 ] investigated the flow structure nearby a rectangular cooling hole on a flat plate and proved that the asymmetric vortex system with a different velocity ratios is stable; and Kwon [ 26 ] measured the heat transfer performance of the coolers for three electronic device configurations with varied jet velocity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Assoudi (2015) believed that the standard − model is more appropriate for the prediction of the turbulent offset jet with small offset ratio (the offset ratio is 0.8 in this paper). So the standard − turbulence model presented by Launder and Spalding (1972) was used.…”
Section: Governing Equationsmentioning
confidence: 99%
“…Agelin-Chaab and Tachie [7] reported that, in the early region of the flow development, the Reynolds number and the offset ratio have significant effects on the decay of the maximum mean velocity, but the decay and spread rates were found to be nearly independent of the offset ratio at lager downstream distances. Assoudi et al [8] had investigated the mean velocity and turbulence characteristics of the turbulent offset jet using PIV technique at 3 velocity ratios and 2 offset ratios; their results indicated that increasing the offset ratio gives a better distribution of the jet within the flow field, giving rise to a better dynamic mixture. Nyantekyi-Kwakye et al [9] studied experimentally the jet with different height ratios (0, 2 and 4); their work revealed that the large scale structures within the inner layer increase with wall normal distance from the pool bottom.…”
Section: Introductionmentioning
confidence: 99%